2006
DOI: 10.33899/rden.2006.39790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental fluorosis among primary school children in Thamar– Yemen.

Abstract: Aims: To determine the prevalence and severity of dental fluorosis in relation to age and sex for primary school children, aged 6-12 years old in Thamar-Yemen. Material and methods: The study included 600 primary school children aged 6, 9 and 12 years old randomly selected (300 males, 300 females) in Thamar-Yemen, who had lived since birth in moderate natural fluoride level (1.8-2.2 ppm) by the use of Dean index to assess dental fluorosis. Results: Showed that the prevalence of dental fluorosis was 19.83 % and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
4
4
1
Order By: Relevance
“…4 The dft value was 1.84 which was less compared to the study by Salman FD. 5 The DMFT value was 0.32 which was similar to the study by Baginska et al 6 but was less compared to others. [7][8][9][10][11] It was observed that dt, ft and dft were more in males compared to females which was similar to other studies 5,12 whereas ds and dfs were more in females compared to males.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4 The dft value was 1.84 which was less compared to the study by Salman FD. 5 The DMFT value was 0.32 which was similar to the study by Baginska et al 6 but was less compared to others. [7][8][9][10][11] It was observed that dt, ft and dft were more in males compared to females which was similar to other studies 5,12 whereas ds and dfs were more in females compared to males.…”
Section: Discussionsupporting
confidence: 83%
“…5 The DMFT value was 0.32 which was similar to the study by Baginska et al 6 but was less compared to others. [7][8][9][10][11] It was observed that dt, ft and dft were more in males compared to females which was similar to other studies 5,12 whereas ds and dfs were more in females compared to males. Females had higher DT and DS as well as higher DMFT/DMFS compared to males which was opposite to the study by Salman FD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The dental fluorosis in permanent dentition was found mostly in 9-10-year-old children (38.6%) similar to other study like in a study by Reddy et al 16 . The result of actual prevalence of dental fluorosis, higher (38.36) in permanent than in primary dentition (13.5%), was similar to study done by Salman 17 .…”
Section: Discussionsupporting
confidence: 87%
“…There is also mounting evidence that dental fluorosis in it's more advanced stages render the teeth more susceptible to cavities as noted by many resources (6)(7)(8) but in general fluoride prevents tooth decay by changing the structures of enamel in infant, making it more resistant to acid attack. It also encourages the remineralization of teeth and may inhibit enzymes used by bacteria to form acid (9)(10)(11) .…”
Section: Natural Fluoride Content Of Drinking Water In Two District Areas In Iraq and Yemen (A Comparative Study)mentioning
confidence: 99%